The nutritional adequacy of vegetarian menu substitutions in urban Kansas childcare centers - Jindrich, Caitlin (Kansas State University, 2021)
Background: Interest in plant-based eating and vegetarianism has increased in recent years. However, little is known of how this trend has impacted childcare foodservice operations. Although vegetarian meals can be nutrient dense, without proper planning, nutrient inadequacies may occur. The purpose of this study was to: (1) characterize vegetarian menu substitution practices within the childcare setting, and (2) compare the diet quality and nutrient content of standard childcare lunches with that of vegetarian alternative lunches. Methods: This was a two-phase cross-sectional study. In phase one, an online survey was used to characterize childcare foodservice operations as they relate to vegetarian menu substitutions and to identify centers currently providing vegetarian alternative lunches. The survey was sent to 155 urban Kansas childcare centers participating in the Child and Adult Care Food Program (CACFP). In phase two, menu data were obtained from the centers that regularly provided a vegetarian meal alternative. Student’s t-tests (P ≤ .05) were used to detect differences in Healthy Eating Index (HEI)-2015 scores and nutrient content based on meal type. Results: Representatives from (N = 85) centers answered the online survey, yielding a response rate of 54.8%. When asked how frequently a vegetarian alternative was offered in lieu of the main meat-containing meal, only 18.5% of centers answered, “three or more times per week”, and 41.2% indicated they “never provide a vegetarian alternative”. In phase two, seven childcare centers provided detailed information for a total of 54 meals. The most common vegetarian meal substitution was cheese, which was used to fulfill all or part of the meat/meat-alternative requirement in 74.1% of the meals (n = 20). Compared to the vegetarian alternative meals, HEI-2015 scores were higher for the standard meals, t(44.7) = 2.14, p = 0.038. The vegetarian alternative meals were higher in calories, fat, saturated fat, calcium, and sodium. The standard meals were higher in protein and choline. Conclusions: Important differences in nutrient content were observed between the standard and vegetarian alternative meals. In addition, the vegetarian alternative meals were found to be of lower diet quality. Additional research is needed to better understand how vegetarianism and the plant-based eating trend has impacted childcare foodservice operations on a national level.
Keywords: Vegetarian diet; Child day care centers; Child and Adult Care Food Programs; Menu planning; Healthy diet